Comparison of the effect of two teaching methods on surgical technologist students' learning and satisfaction (flashcards vs. mobile-based learning) - Leila Sadati; Mehran Nafar; Sahar Karami; Mohamad Reza Yazdani; Zahra Nouri Khaneghah (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: M-learning is "learning across multiple contexts, through social and content interactions, using simple hand-held technologies, wireless and mobile network. This personal electronic device is a way to facilitate the transfer of learning and improve teaching. Hence, the researchers decided to design a mobile-based learning application to teach surgical instruments comprehensively and compare students' learning and satisfaction in both mobile-based learning and flashcards methods. MATERIALS AND METHODS: An interventional study was conducted on surgical technologist students in Alborz University of medical science (2019). Students were divided into two groups: flashcards (n = 21) and mobile application learning group (n = 21). The difference of pre- and post-test scores was considered for the evaluation of learning level in two groups. Data were entered into SPSS 20.0 software and analyzed by statistics tests.Data were analyzed by a paired t-test, independent t-test, and Pearson's correlation coefficient. RESULTS: There was no significant difference in students' knowledge level between two groups before intervention (P = 0.87) but there was significant difference between groups after the intervention (P = 0.003). In the evaluation of student's satisfaction, the mobile application was preferred by 84.28% of students. CONCLUSION: Given the effectiveness of using both methods (flashcards and mobile application), it is recommended that these methods especially mobile application be used for surgical instruments education.